The hydrolysis of primary sewage sludge under biosulphidogenic conditions - Molwantwa, Jennifer Balatedi (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2003)
The potential for using readily available and cost-effective complex carbon sources such as primary sewage sludge for a range of environmental remediation processes, including biological sulphate reduction, biological nutrient removal and the bioremediation of acid mine drainage, has been constrained by the slow rate of solubilization and low yield of soluble products, which drive the above mentioned processes. Previous work conducted by the Environmental Biotechnology Group at Rhodes University indicated that the degradation of primary sewage sludge was enhanced under sulphate reducing conditions. This was proven in both laboratory and pilot-scale (Reciprocating Sludge Bed Reactor) systems, where the particulate matter accumulated in the sludge bed and the molecules in smaller flocs were rapidly solubilized. The current study was aimed at investigating in more detail the factors that govern the enhanced hydrolysis under sulphate reducing conditions, and to develop a descriptive model to explain the underlying mechanism involved. The solubilization of primary sewage sludge under sulphate reducing conditions was conducted in controlled flask studies and previously reported findings of enhanced hydrolysis were confirmed. The maximum percentage solubilization obtained in this study was 31% and 63% for the methanogenic and sulphidogenic systems respectively, and this was achieved over a period of 10 days. A rate of reducing sugar production and complex molecule breakdown of 51 mg. Lâ »Â¹.hrâ »Â¹ and 167 mg.Lâ »Â¹.hrâ »Â¹ was observed for the methanogenic and sulphidogenic systems respectively. The flask studies revealed that during hydrolysis of primary sewage sludge under sulphidogenic conditions there was enhanced production of soluble products, specifically carbohydrates (reducing sugars) and volatile fatty acids, compared to methanogenic conditions. The rate at which these products were utilized was also found to be more rapid under sulphidogenic as compared to methanogenic conditions. A study of the distribution of volatile fatty acids indicated that acetate was utilized preferentially in the methanogenic system, and that propionate, butyrate and valerate accumulated with time. The converse was found to occur in the sulphidogenic system. The descriptive model developed from the results of this study was based on the fact that a consortium of bacteria, composed of hydrolytic, acidogenic and acetogenic species, carries out the solubilization of complex carbon sources. Furthermore, it is essential that equilibrium between product formation and utilization is maintained, and that accumulation of soluble end products impacts negatively on the rate of the hydrolysis step. It is therefore proposed that the relatively poor utilization of VFA and reducing sugars in the methanogenic system activates a negative feedback inhibition on the hydrolytic and/ or acidogenic step. This inhibition is reduced in the sulphidogenic system where the utilization of end products is higher.
Keywords: Sewage sludge; Hydrolysis; Sewage -- Purification -- Activated sludge process